Endodontic Management of Maxillary Central Incisor with Two Roots, and Lateral Incisor with a C-shaped Canal; A Case Report: . - Mahadevan, Mageshwari; Paulaian , Benin; Madhavankutty Santhakumari , Ravisankar; Kumar Alexander, Arvind; Neelamani Jaya , Nagaraj (Iranian Endodontic Journal, 2023)
The knowledge of anatomical variations in the morphology of root canal systems can affect the successful diagnosis to deliver proper endodontic treatment. The current case report enlightens the endodontic management of an anomalous maxillary left central incisor with two roots/root canals, a C-shaped root canal configuration in a maxillary left lateral incisor identified by three-dimensional cone-beam computed tomography imaging as well as the successful aesthetic rehabilitation of maxillary fractured incisors. The chief complaint of patient was a history of trauma during his outdoor play and consequent broken upper front teeth. Tooth #9 was diagnosed with pulpal necrosis accompanied by asymptomatic apical periodontitis with two relatively dilacerated roots while the maxillary left lateral incisor (tooth #10) was diagnosed with necrotic pulp and asymptomatic apical periodontitis having a C-shaped canal. Endodontic treatment for teeth #9 and #10 were performed, followed by post and core fabrication. Tooth reinforcement was achieved with prefabricated un-polymerized glass fiber post for lateral incisor and Interlig Fiber for central incisor. Intentional root canal treatment of tooth #8 was considered to reduce labial inclination. The anomalous maxillary central incisor with two roots is an unexpected variant during endodontic treatment, and the presence of C-shaped canal in lateral incisors is extremely rare requiring careful diagnosis with radiographs, clinical examination along with additional aids; e.g. Three-dimensional (3-D) cone-beam computed tomography. 3-D imaging has added the advantages of appropriate identification of anomalous anterior teeth and careful location of additional root canal(s) during endodontic treatment.